Study on the law that govern the safety and health of workers in Malaysia / Nurhani Mohamad Shukri … [et al.] - Mohamad Shukri, Nurhani; Abd Rahman, Nurul Hazirah; Azman, Nur Nadia Shamira; Zainal Abidin, Laily Izyan (2013)
This research mainly focuses on the law governed safety and health in workplace in Malaysia. It covers the general review of the defects of OSHA 1994 which is the main regulation governing this issue. This research deals with the defect of the law itself and how to improve the effectiveness of the law in order to provide a better coverage on the issue of safety and health in the workplace. To provide a general standard of how the law can provide the best protection and prevention from any risk of accident and health issue in the workplace this paper would make a general comparison of the law under Malaysian OSHA 1994 with the law and regulation in ILO Convention on Safety and Health and also comparison with the United Kingdom. ILO Convention on Safety and Health is regarded as the standard to follow for effective protection of the workers in the workplace, while the United Kingdom will provide a general view of effective application of the law. From the current situation, it is an evident that the standard of protection provided for the workers in Malaysia is still lacking and need more improvement. It is a pertinent issue to be studied due to the fact that, workers are regarded as the most valuable asset of the economy of our country. This study hopes to assist the policy makers in improving the level of protection of workers in their workplace in Malaysia.